Comparing teacher autonomy in different models of educational governance - Ana Lucia Lennert da Silva (Taylor & Francis Group, 2021)
This article addresses teacher autonomy in different models of educational governance using quantitative data from the OECD TALIS 2018 and qualitative data from a study on teacher autonomy conducted in Norway and Brazil. In this article, teacher autonomy is seen as a multidimensional concept referring to decision-making and control in relation to state governance. Further, the different degrees of implementation of accountability measures across countries determine the models of educational governance. The quantitative data reveals no clear pattern between teacher autonomy and models of educational governance. In general, teachers perceive that they have good control over teaching and planning at the classroom level. However, teachers report that they participate to a lesser degree in professional collaboration in schools, which could allow for collegial teacher autonomy. Teachers also report low perceived social value and policy influence, which may provide insight into professional teacher autonomy at the policy level. This article also shows the relevance of a detailed description of the country cases to gain a better understanding of the multiple dimensions of teacher autonomy.